Investigating the Ridership Impact of New Light-Rail Transit and Arterial Bus Rapid Transit Lines in the Twin Cities. Issue 7 (July 2022) - Berrebi, Simon Jonas; Lind, Eric; Brakewood, Candace; Erhardt, Gregory; Watkins, Kari
Cities in the United States and across the world are investing in high-capacity modes with enhanced reliability, including light-rail transit (LRT) and arterial bus rapid transit (BRT), to regain ridership. However, the impact of replacing high-frequency bus service with these modes is not well understood. This paper investigates the ridership effect of implementing LRT and arterial BRT on corridors that were already well served by local bus routes. Using data from Metro Transit in Minneapolis/Saint Paul between 2012 and 2017, overall ridership and frequency on the corridors are evaluated to distinguish between trips that were newly generated and trips that were drawn from the local bus routes running in the same corridor. Fixed-effects models are fitted to estimate how much of the new ridership can be attributed to the high-capacity modes and to the reliability improvements they provide while controlling for covariates. Results show that the Green Line LRT generated 86% more ridership and the arterial BRT A Line generated 12% more ridership than if the transit agency had relied on local bus service. These results demonstrate the potential ridership impacts of replacing and supplementing existing bus service with reliable high-capacity modes.